UMP forging ahead - T.N., Alagesh (The New Straits Times Press (M) Bhd., 2017)
Universiti Malaysia Pahang's (UMP) appointment as the Focal University for the inaugural East Coast Rail Link Industrial Skills Training Programme (PLKI-ECRL) speaks volumes about the 15-years-old higher learning institution.